RFIC and MMIC design and technology - Robertson, I. D. (Ian D.).; Lucyszyn, S. (Stepan). (London, United Kingdom Institution of Engineering and Technology, 2001)
The following topics are dealt with: devices and fabrication technology; passive components; CAD techniques; amplifiers; oscillators; mixers; switches and attenuators; phase shifters; integrated antennas; transceivers; and measurement techniques.
Previous ed. published as: MMIC design. 1995.
Electronic reproduction.
Keywords: Microwave integrated circuits -- Design and construction; Electronic books